In an AP, if the ${m^{th}}$ term is n and ${n^{th}}$ term is m, then find the pth term. ($m \ne n$).
Answer
Verified
482.4k+ views
Hint: Following the question we will get two equations. Subtracting them we will get the value of d and putting d value in one equation we will get the first term of the sequence. Substituting them in the general formula we will get the answer.
Complete step-by-step answer:
We know that in arithmetic progression, the general formula is,
${a_n} = a + (n - 1)d$
Where, ${a_n}$ = ${n^{th}}$ term of AP
a = first term of the AP
d = common difference in AP
Thus ${m^{th}}$ term, ${a_m} = a + (m - 1)d$
In the question it is given that ${m^{th}}$ term is n
i.e. $a + (m - 1)d = n$………………….(1)
And ${n^{th}}$ term, ${a_n} = a + (n - 1)d$
It is also given in the question that ${n^{th}}$ term is m
I.e. $a + (n - 1)d = m$………………..(2)
Subtracting equation (2) from equation (1) we find the common difference of the arithmetic series.
Hence, $[a + (m - 1)d] - [a + (n - 1)d] = n - m$
$ \Rightarrow a + (m - 1)d - a - (n - 1)d = n - m$
Cancelling a and –a in left hand side we get,
$(m - 1)d - (n - 1)d = n - m$
Taking d common in left hand side we get,
$(m - 1 - n + 1)d = n - m$
Cancelling -1 and +1 we get,
$(m - n)d = n - m$
$ \Rightarrow d = \dfrac{{n - m}}{{m - n}}$
Multiplying -1 on both side we get,
$d = - 1$
Putting value of d in equation (2) we get,
$a + (n - 1)d = m$
$ \Rightarrow a + (n - 1)\left( { - 1} \right) = m$
$ \Rightarrow a - n + 1 = m$
$ \Rightarrow a = m + n - 1$
We got the value of a and d.
For the ${p^{th}}$ term,
We will use the general formula of AP i.e.
${a_n} = a + (n - 1)d$
Putting n = p, a = m+n-1 and d = -1 in the above formula we get,
${a_p} = \left( {m + n - 1} \right) + \left( {p - 1} \right) - 1$
Expanding the right hand side of the equation we get,
${a_p} = m + n - 1 - p + 1$
Cancelling -1 and +1 in the right hand side we get,
${a_p} = m + n - p$
Thus the ${p^{th}}$ term is ${a_p} = m + n - p$.
Note: Arithmetic progression or arithmetic sequence is the sequence in which the difference between two consecutive numbers are equal.
You can also subtract equation 1 from equation 2 to get the d value.
Be cautious while doing the equations because the mistakes in minus and plus signs can even change the whole answer.
Complete step-by-step answer:
We know that in arithmetic progression, the general formula is,
${a_n} = a + (n - 1)d$
Where, ${a_n}$ = ${n^{th}}$ term of AP
a = first term of the AP
d = common difference in AP
Thus ${m^{th}}$ term, ${a_m} = a + (m - 1)d$
In the question it is given that ${m^{th}}$ term is n
i.e. $a + (m - 1)d = n$………………….(1)
And ${n^{th}}$ term, ${a_n} = a + (n - 1)d$
It is also given in the question that ${n^{th}}$ term is m
I.e. $a + (n - 1)d = m$………………..(2)
Subtracting equation (2) from equation (1) we find the common difference of the arithmetic series.
Hence, $[a + (m - 1)d] - [a + (n - 1)d] = n - m$
$ \Rightarrow a + (m - 1)d - a - (n - 1)d = n - m$
Cancelling a and –a in left hand side we get,
$(m - 1)d - (n - 1)d = n - m$
Taking d common in left hand side we get,
$(m - 1 - n + 1)d = n - m$
Cancelling -1 and +1 we get,
$(m - n)d = n - m$
$ \Rightarrow d = \dfrac{{n - m}}{{m - n}}$
Multiplying -1 on both side we get,
$d = - 1$
Putting value of d in equation (2) we get,
$a + (n - 1)d = m$
$ \Rightarrow a + (n - 1)\left( { - 1} \right) = m$
$ \Rightarrow a - n + 1 = m$
$ \Rightarrow a = m + n - 1$
We got the value of a and d.
For the ${p^{th}}$ term,
We will use the general formula of AP i.e.
${a_n} = a + (n - 1)d$
Putting n = p, a = m+n-1 and d = -1 in the above formula we get,
${a_p} = \left( {m + n - 1} \right) + \left( {p - 1} \right) - 1$
Expanding the right hand side of the equation we get,
${a_p} = m + n - 1 - p + 1$
Cancelling -1 and +1 in the right hand side we get,
${a_p} = m + n - p$
Thus the ${p^{th}}$ term is ${a_p} = m + n - p$.
Note: Arithmetic progression or arithmetic sequence is the sequence in which the difference between two consecutive numbers are equal.
You can also subtract equation 1 from equation 2 to get the d value.
Be cautious while doing the equations because the mistakes in minus and plus signs can even change the whole answer.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE